Quality Assessment of Extemporaneous Capsule Preparation containing Methylprednisolone, CTM, and Theophylline using Spectrophotometrics and Chemometrics Techniques - Muhammad Darmawangzah; Florentinus Dika Octa Riswanto; Irnawati Irnawati (Sanata Dharma University, 2025)
Currently, doctors in developing countries still prefer to prescribe compounding drugs because certain drugs are not available in ready-made dosage forms. It is considered that the capsule formulation can increase patient compliance because it requires a smaller amount of medication. In particular, for asthma patients, extemporaneous capsule preparation containing methylprednisolone, CTM, and theophylline is usually prescribed. However, theophylline, which has a narrow therapeutic index, combined with small doses of methylprednisolone and CTM, may result in inconsistent drug content in the compounded drug. This study aimed to assess the quality of the capsule mixture containing methylprednisolone, CTM, and theophylline formulated at the “X” Kolaka Community Health Center, Southeast Sulawesi, Indonesia. Extemporaneous capsules are tested using various methods such as organoleptic tests, water content tests, disintegration time tests, and content uniformity tests of compounding drugs. The quality test results of the compounding capsule with the active substance a combination of methylprednisolone, CTM, and theophylline formulated at the “X” Kolaka Health Center met the quality requirements with organoleptic tests, moisture content tests, and disintegration time tests. The content uniformity test does not meet the requirements according to the Indonesian Pharmacopoeia VI edition based on the acceptance values of L1% and L2%.